Enhanced catalytic performance and reduced by-products emission on plasma catalytic oxidation of high-concentration toluene using Mn-Fe/rGO catalysts. Issue 6 (December 2022) - Liu, Zongyang; Zhang, Yalan; Jiang, Shengyu; Liu, Shengyu; Cao, Jing; Ai, Yingwei
Abstract: High-concentration toluene is refractory to mineralize and must be controlled. The synergistic catalytic degradation of toluene with dielectric barrier discharge (DBD) results in the creation of large quantities of O3 and NOx . In this study, reduced graphene (rGO)-based catalysts with Mn and Fe (Mn-Fe/rGO) were recommendable. The effect of Mn-Fe/rGO catalysts on DBD oxidation of toluene was studied by changing Mn-Fe molar ratios and total loading. We investigated the performance of Mn-Fe/rGO catalysts on DBD oxidation of toluene by varying the Mn-Fe molar ratios and the total loading. The Mn-Fe molar ratio was 3:1, loading was 10 wt%, maximum toluene conversion was 85%, and COx selectivity was as high as 69.8%. When energy density (ED) was 598.25 J/L and toluene concentration was 657.14 mg/m 3, toluene conversion, COx selectivity, O3 conversion, NO2 conversion, and NO conversion were 85.6%, 68.9%, 82.5%, 68.2%, and 64.3%, respectively. Analyzing the gas chromatography-mass spectrometric (GC-MS) data and determining the tail gas mechanism, it was found that toluene ring-opening was synergistic between active substances and Mn-Fe/rGO catalysts. Ferromanganites not only promoted the ring-opening degradation of toluene, but also had a positive effect on O3 conversion and NOX conversion. They consume aldehydes and NOX, produce O·and N·, and thus facilitate the mineralization process. This study provides new insights into plasma catalytic oxidation of high-concentration organic pollutants. Graphical Abstract: Reduced Graphene (rGO)-based Catalysts with Mn and Fe (Mn-Fe/rGO) convert plasma by-products to harmless products and improve the efficiency of degrading high-concentration toluene, Mn-Fe/rGO were recommendable. ga1 Highlights: Plasma catalytic oxidation of high-concentration toluene and reduction of by-product emissions Mn-Fe/rGO catalysts combined with DBD are used to degrade high-concentration toluene. The Mn: Fe ratio of 3:1 enhances the catalytic oxidation capacity and reduces DBD energy consumption. The emission of O3, NO and NO2 generated by DBD is alleviated. Plasma catalytic oxidation mechanism of high-concentration toluene was proposed.